The Association Between Serum HMGB2 Levels and Abdominal Aortic Aneurysm in Males: Insights Into the HMGB2–TREM Pathway - Liting Pan; Junji Chen; Yanjun Sun; Fang Wang (Reviews in Cardiovascular Medicine)
Background: Abdominal aortic aneurysm (AAA) is a major public health challenge and presents high mortality due to diagnostic and therapeutic difficulties. This study investigated the role of high-mobility group box2 (HMGB2) and the HMGB2-triggering receptor expressed on the myeloid cell (TREM) pathway in male AAA patients. The goal was to evaluate HMGB2 as a novel biomarker and to elucidate its contribution to the pathogenesis of AAA. Our findings offer new insights into AAA biology and highlight the potential application of HMGB2 for early detection and therapeutic targeting. Methods: This retrospective case–control study included 36 male AAA patients and 41 male controls with balanced baseline characteristics. HMGB1, HMGB2, soluble TREM-1 (sTREM-1), and sTREM-2 serum levels were measured by enzyme-linked immunosorbent assay (ELISA). The association between HMGB2 and AAA was analyzed using multivariate logistic regression, while the diagnostic performance of HMGB2 was assessed using receiver operating characteristic (ROC) curves. Results: Elevated HMGB2 and HMGB1 levels were associated with higher risks of AAA (HMGB2: OR: 1.158, 95% CI: 1.011–1.325; p < 0.05; HMGB1: OR: 1.275, 95% CI: 1.048–1.551; p < 0.05) and aneurysm rupture (HMGB2: OR: 1.117, 95% CI: 1.005–1.241; p < 0.05; HMGB1: OR: 1.212, 95% CI: 1.003–1.465; p < 0.05). Meanwhile, sTREM-1 exhibited a negative correlation with AAA (OR: 0.991, 95% CI: 0.985–0.997; p < 0.01). The odds ratios of the fourth quartile HMGB2 and HMGB1 levels for AAA were 6.925-fold and 8.621-fold higher, respectively, than the first quartile levels. The HMGB2 serum level was positively correlated with a larger AAA diameter, with the diameter increasing progressively as the HMGB2 level increased. The area under the ROC curve (AUC) for predicting AAA was 0.713 for HMGB2, 0.677 for HMGB1, and 0.665 for sTREM-1. HMGB1 and sTREM-1 both correlated with HMGB2. Each HMGB1 quartile group exhibited a significant increase as HMGB2 increased. Further, sTREM-1 significantly increased at low to moderate HMGB2 levels but decreased in the highest HMGB2 quartile. Conclusion: Elevated HMGB2 serum levels are independently associated with the incidence of AAA in males. HMGB2–TREM pathway disruption may play a critical role in AAA pathogenesis.